The Halophyte Dehydrin Sequence Landscape - Siwar Ghanmi; Steffen P. Graether; Moez Hanin (Biomolecules, 2022)
Dehydrins (DHNs) belong to the LEA (late embryogenesis abundant) family group II, that comprise four conserved motifs (the Y-, S-, F-, and K-segments) and are known to play a multifunctional role in plant stress tolerance. Based on the presence and order of these segments, dehydrins are divided into six subclasses: YnSKn, FnSKn, YnKn, SKn, Kn, and KnS. DHNs are rarely studied in halophytes, and their contribution to the mechanisms developed by these plants to survive in extreme conditions remains unknown. In this work, we carried out multiple genomic analyses of the conservation of halophytic DHN sequences to discover new segments, and examine their architectures, while comparing them with their orthologs in glycophytic plants. We performed an in silico analysis on 86 DHN sequences from 10 halophytic genomes. The phylogenetic tree showed that there are different distributions of the architectures among the different species, and that FSKn is the only architecture present in every plant studied. It was found that K-, F-, Y-, and S-segments are highly conserved in halophytes and glycophytes with a few modifications, mainly involving charged amino acids. Finally, expression data collected for three halophytic species (Puccinillia tenuiflora, Eutrema salsugenium, and Hordeum marinum) revealed that many DHNs are upregulated by salt stress, and the intensity of this upregulation depends on the DHN architecture.